THE BIOLOAD AND AFLATOXIN CONTENT OF HERBAL MEDICINES FROM SELECTED STATES IN NIGERIA - Ezekwesili-Ofili, J O; Onyemelukwe, N F; Agwaga, P; Orji, I (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: There is increased reliance on traditional herbal medicines by several millions of people worldwide, especially in West Africa and Nigeria in particular. This is due to escalating cost of good quality drugs and consequent proliferation of faked cheaper drugs. However, non standardization of production and handling methods have resulted in herbal medicines with varying quality and safety indices, thus resulting in possible public health concerns. This work investigated the microbial load and aflatoxin levels in herbal medicines from selected states in Nigeria. Materials and Methods: A total of 210 samples obtained from various renowned herbal medicine practitioners from some selected states in Nigeria, based on their medicinal uses, were analyzed to determine the microbial load by the plate count method and aflatoxin contamination levels using thin layer chromatography with aflatoxin standards. Results: At least six bacterial genera (Bacillus, Pseudomonas, Salmonella, EPEC, EHEC, Streptococcus and other coliforms) and 6 fungal genera (Aspergillus, Penicillium, Rhizopus, Cladosporium, Geotricum and Candida) were isolated. Aflatoxin B1, B2 and G1 were detected in varying concentrations in the samples analyzed, with an average occurrence of 18.6%. Some of these herbal concoctions were found to contain unacceptably high bioload, according to WHO standards. Conclusion: Microbial contamination and the presence of aflatoxins in herbal medicines appear to be an endemic problem in Nigeria, as observed in this work, probably due to poor observation of basic hygiene during preparations and poor storage conditions. The findings in this work may serve in developing and instituting public health standards for the production and safety of herbal remedies in Nigeria.